Synthesis of Hydroxyapatite From Chicken Bones Using the High Temperature Method - Riyanda Bagus Setiawan; Faishal Zhafran Mumtaz; Lilik Suprianti; Ramadhani Mahendra Kusuma (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2026)
This study investigates the syntesys of hydroxyapatite (HAp) from chicken bone waste, which is abundantly available due to high poultry production, using a high-temperature method. The objective of this study was to determine the effect of variations in sintering temperature (300, 400, 500, and 600°C) and sintering time (3, 4, 5, 6, and 7 hours) on the yield and Ca/P ratio of the HAp produced. The prepared chicken bone powder was first calcined at 900°C for 3 hours before sintering. The results showed that the optimal conditions were 600°C for 7 hours, characterized by a change in the sample's colour to white and a yield of 69%. XRF analysis confirmed the formation of HAp with a Ca/P ratio of 1.69. It was concluded that a sintering temperature of 600°C for 7 hours is optimal for producing pure HAp from chicken bone waste. Contribution to Sustainable Development Goals (SDGs):SDG 3: Good Health and Well-beingSDG 9: Industry, Innovation and InfrastructureSDG 12: Responsible Consumption and Production